Pedagogical Meditations (From the Experience of Teaching Scientific Communism) - Lempertas, Izraelis (Problemos, 1974)
The success of a lecture lies in the contact with the audience. The paper analyses the way this contact is made. Methodical skill provides the “feeling of the audience” to the lecturer but largely it comes from his knowledge of the peculiarities of the audience. The modem type of a student is the intellectual having a particular frame of mind and particular ways of assimilating the subject matter. Although this category is not predominant it is the one which constitutes the psychological climate in a group and it is the one upon which the teacher ought to orientate himself in the main. This requires intellectual intensity and logical soundness of a lecture. The author sees the solution of the bias problem with regard to different specialities in taking account of specific habits of thought characteristic of students of different faculties and not in the choice of the specifically orientated subject matter.